2017
DOI: 10.1080/10428194.2017.1324154
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic T cells in chronic idiopathic neutropenia express restricted antigen receptors

Abstract: Chronic idiopathic neutropenia (CIN) is an acquired disorder of granulopoiesis characterized by female predominance and mostly uncomplicated course. Crucial to CIN pathophysiology is the presence of activated T lymphocytes with myelosuppressive properties in both peripheral blood (PB) and bone marrow (BM). We systematically profiled the T cell receptor beta chain (TRB) gene repertoire in CD8 cells of 34 CIN patients through subcloning/Sanger sequencing analysis of TRBV-TRBD-TRBJ gene rearrangements. Remarkable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“… 14 The acquired disorders are most commonly considered autoimmune/idiopathic diseases, with autoantibodies or lymphocyte-derived cytokines impairing neutrophil production at the latter stages of their development. 23 …”
Section: Discussionmentioning
confidence: 99%
“… 14 The acquired disorders are most commonly considered autoimmune/idiopathic diseases, with autoantibodies or lymphocyte-derived cytokines impairing neutrophil production at the latter stages of their development. 23 …”
Section: Discussionmentioning
confidence: 99%
“…In order to obtain evidence as to whether the herin identified T cell clones might have expanded in response to CLL-associated antigens or not, we performed extensive comparisons against not only CLL/MBL sequence datasets, 36,41 but also datasets from common herpes virus infections (CMV/EBV), healthy individuals, and entities mediated by T cell clones. 30,[32][33][34][35][37][38][39][40] and found a significant number of major T cell clonotypes shared exclusively among CLL patients. This is remarkable given: (i) the random HLA background of our cohort, and (ii) the size of the comparison dataset (761,968 distinct TRBV-TRBD-TRBJ sequences).…”
Section: Discussionmentioning
confidence: 99%
“…We determined the major clonotypes of all CLL samples included in the study (n=563 unique clonotypes, i.e. 10 major clonotypes of each sample removing duplicate values such as clonotypes which persisted in overtime analysis of the same patient or clonotypes shared among different patients) and compared them across CLL patients of this cohort, and against: (i) all T cell clonotypes from our previous NGS study involving treatment-naive CLL patients (n=1,105,728), 28 (ii) T cell clonotypes from 15 healthy donors (NGS study by our group, n=573,651), 32 (iii) HHV-4 (Ebstein-Barr virus, EBV), HHV-5 (cytomegalovirus, CMV), and BK virus-specific T cell clonotypes (anti-viral T cell NGS study by our group, n=169,502), 33 (iv) nonredundant, well-annotated, unique T cell clonotypes retrieved from public databases (n=17,024), 34,35 and (v) T cell clonotypes from previous low-throughput immunoprofiling studies (classic subcloning followed by Sanger sequencing) in clinical monoclonal B cell lymphocytosis (high-count MBL, n=545), 36 as well as clinical entities associated with clonal T cell expansions [R-LON (n=283), 30 chronic idiopathic neutropenia (CIN, n=576), 37 large granular T cell leukemia (Τ-LGL, n=932)]. [38][39][40]…”
Section: Inter-patient and Across Entities Clonotype Comparisonmentioning
confidence: 99%
“…14,63 The sequencing analysis of the TRB CDR3 has also revealed shared clonotypes between different CIN patients, possibly suggesting a common underlying antigen stimulation. 64,65 However, not only T-cell expansions but also myeloid cell populations may contribute to the immune processes associated with CIN. It has thus shown that the monocyte cell subsets are altered in CIN patients and consist of decreased number of classical CD14 bright /CD16 − and increased intermediate CD14 bright / CD16 + and nonclassical CD14 dim /CD16 + cells.…”
Section: Chronic Idiopathic Neutropeniasmentioning
confidence: 99%
“…14,63 The sequencing analysis of the TRB CDR3 has also revealed shared clonotypes between different CIN patients, possibly suggesting a common underlying antigen stimulation. 64,65…”
Section: Mechanisms For Ainmentioning
confidence: 99%